Water column raw data (Kongsberg EM710 entire dataset) of RV METEOR during cruise M191 - Jörg Geldmacher; Aaron Micallef; Christian Timm; Mia Schumacher (PANGAEA, 2024)
Raw water column data were collected aboard RV METEOR during cruise M191 using a Kongsberg EM 710 multibeam echosounder. The expedition took place during 16.07.2023 – 05.08.2023 from Algeciras (Spain) to Piraeus (Greece) in the Mediterranean. The main objective of M191 was to extensively map the seafloor (with multibeam echo sounder, sediment echo sounder, and towed magnetometer) and sample (by chain bag dredging) unexplored volcanic structures along the Sicilian Channel Rift Zone (Pantelleria-, Malta- and Linosa-Graben) and the Capo-Granitola-Sciacca Fault Zone (CGSFZ). Data were recorded in the Italian and Greek EEZ. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.